Influence of thermal treatment on the physicochemical and functional properties of tea polysaccharide conjugates. (October 2021) - Li, Qian; Shi, Jinglan; Li, Jing; Liu, Lu; Zhao, Tiantian; McClements, David Julian; Fu, Yinxin; Wu, Zhengqi; Duan, Mengran; Chen, Xiaoqiang
Abstract: With increasing consumer demand for label-friendly products, there is a push towards the identification and utilization of effective natural emulsifiers from botanical sources. In this study, we investigated the effect of controlled thermal treatments on the physicochemical and functional properties of tea polysaccharide conjugates (TPCs). Thermal treatment of the TPCs at 110 °C for 3 days (TPC-3d) markedly improved their emulsifying activity without negatively impacting their antioxidant activity. In comparison with animal-based (sodium caseinate) and synthetic (Tween 80) emulsifiers, TPC-3d stabilized emulsions were more effective at inhibiting the chemical degradation of encapsulated ω-3 oils and curcumin during storage at elevated temperatures. The improvement in the chemical stability of the bioactive lipids was mainly ascribed to the antioxidant activity of the conjugated phenolic groups in the TPC. Our results show that thermally-treated TPC has the potential to be used as a novel plant-based antioxidant emulsifier to encapsulate and protect chemically labile hydrophobic compounds. Graphical abstract: Image 1 Highlights: ● The impact of heating on tea polyphenol conjugate (TPC) functionality was studied ● Thermal treatment did not negatively influence TPC antioxidant activity ● Thermal treatment (110 °C, 3 days) improved TPC emulsifying activity ● In emulsions, TPC inhibited ω-3 oil oxidation and curcumin degradation